Epistemological Perspectives in Inclusive Education: A Systematic Review of Differentiated Instruction Practices Across Contexts - Fuji Lestari; Mahdum Mahdum; Jimmi Copriady (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study situates inclusive education within broader epistemological debates, emphasizing how differing conceptions of knowledge shape differentiated instruction practices across diverse educational contexts . The purpose of this systematic review is to examine how empiricist, constructivist, and hybrid epistemological orientations influence the design and implementation of differentiated instruction in inclusive settings, and to identify contextual factors mediating this relationship. Employing PRISMA 2020 guidelines, a systematic search of the Scopus database (2019–2024) yielded 43 peer-reviewed studies, which were analyzed through thematic synthesis and comparative frameworks. The findings reveal three dominant orientations: constructivist approaches (44%) emphasize student-centered, flexible, and experiential learning; empiricist approaches (30%) prioritize data-driven, structured, and assessment-based practices; while hybrid approaches (26%) integrate both perspectives pragmatically. The review further identifies teacher preparation, policy frameworks, and governance structures as key mediating factors influencing how epistemological beliefs translate into classroom practice. Notably, only 28% of studies reported explicit teacher reflection on epistemological foundations, indicating a gap between theory and practice. The study concludes that epistemological orientations fundamentally shape differentiated instruction and inclusive education outcomes. It proposes the Epistemology-Practice-Context (EPC) model to conceptualize the dynamic interaction between beliefs, contextual conditions, and pedagogical practices. These findings highlight the need for enhancing teachers’ epistemological literacy and aligning policy frameworks with diverse educational contexts to improve the effectiveness of inclusive education.